Adsorption of p-nitrophenols (PNP) on microalgal biochar: Analysis of high adsorption capacity and mechanism. (November 2017) - Zheng, Heshan; Guo, Wanqian; Li, Shuo; Chen, Yidi; Wu, Qinglian; Feng, Xiaochi; Yin, Renli; Ho, Shih-Hsin; Ren, Nanqi; Chang, Jo-Shu
Graphical abstract: Highlights: PNP adsorption behaviors by microalgae and their derived biochars are compared. Biochar derived from Chlorella sp. Cha-01 has excellent PNP adsorption ability. Polar binding sites of the microalgal biochars contribute to PNP adsorption ability. Abstract: Biochars derived from three microalgal strains (namely, Chlorella sp. Cha-01, Chlamydomonas sp. Tai-03 and Coelastrum sp. Pte-15) were evaluated for their capacity to adsorb p-nitrophenols (PNP) using raw microalgal biomass and powdered activated carbon (PAC) as the control. The results show that BC-Cha-01 (biochar from Chlorella sp. Cha-01) exhibited a high PNP adsorption capacity of 204.8 mg g −1, which is 250% and 140% higher than that of its raw biomass and PAC, respectively. The adsorption kinetics and equilibrium are well described with pseudo-second-order equation and Freundlich model, respectively. BC-Cha-01 was found to contain higher polarity moieties with more O-containing functional groups than PAC and other microalgae-derived biochars. The strong polarity of binding sites on BC-Cha-01 may be responsible for its superior adsorption capacity. The biochars from Chlorella sp. Cha-01 seem to have the potential to serve as a highly efficient PNP adsorbent for wastewater treatment or emergency water pollution control.